Opportunities and challenges for the asset management industry - Singapore Management University (Institutional Knowledge at Singapore Management University, 2011)
With the secular rise of Asia and a deluge of capital inflows, amid a backdrop of battered global financial markets, bankers, asset managers, academics and investors gathered to hear and discuss the opportunities and challenges facing the asset management industry in Asia. Organised by the Centre for Asset Securitisation and Management in Asia(CASA), under SMU's Sim Kee Boon Institute for Financial Economics, the inaugural asset management conference hosted a panel of experts.